White light generation in Tm3+/Ho3+/Yb3+ doped PbO-GeO2 glasses excited at 980 nm - Camilo, M. E. [UNESP]; Silva, E. de O. [UNESP]; Assumpcao, Thiago A. A. de [UNESP]; Kassab, Luciana R. P. [UNESP]; Araujo, Cid B. de (American Institute of Physics (AIP), 2013)
We report white light generation (WLG) in Tm3+/Ho3+/Yb3+ doped PbO-GeO2 glass under continuous-wave excitation at 980 nm. Intense blue (approximate to 477 nm), green (approximate to 545 nm), and red (approximate to 658 nm) emissions were simultaneously observed at room temperature. The blue light is mainly due to the Tm3+ transition (1)G(4) -> H-3(6). The green emission is due to the Ho3+ transitions (S-5(2), F-5(4)) -> I-5(8) and the red luminescence is due to the Ho3+ transition F-5(5) -> I-5(8) and transition (1)G(4) -> F-3(4) associated to the Tm3+ ions. Energy transfer processes from Yb3+ to Ho3+ and Yb3+ to Tm3+ ions were responsible for the WLG. Adjusting the relative concentration of the rare-earth (RE) ions, we could obtain emission in the white region of the CIE chromaticity diagram. The present results indicate that PbO-GeO2 glass has large potential to be used for white displays. (C) 2013 AIP Publishing LLC.